Q-marker identification of Paris polyphylla var. yunnanensis (Franch.) Hand.-Mazz. in pulmonary metastasis of liver cancer mice. (15th July 2022) - Wang, Genbei; Yan, Mengyao; Hao, Ruijia; Lv, Panpan; Wang, Yu; Man, Shuli; Gao, Wenyuan
Abstract: Ethnopharmacological relevance: Rhizoma Paridis saponins (RPS) as the mainly active components of Paris polyphylla var. yunnanensis (Franch.) Hand.-Mazz., possess tumor therapeutic potential. However, the anti-tumor material basis of RPS in liver cancer pulmonary metastasis remains poorly understood. The objective of this study was to identify the distribution and anti-cancer effects of RPS in liver cancer pulmonary metastatic model. Materials and methods: In this study, a mouse liver cancer pulmonary metastasis model was established to determine the distribution of different saponins in the tissues by UPLC-MS and plasma protein binding rate. Results: As a result, RPS prolonged the survival time and inhibited the pulmonary metastasis in H22 injected mice through its underlying mechanism. UPLC-MS identified saponins from RPS such as PVII, PH, PVI, PII, gracillin and PI in tissues, which may be regarded as the Q-markers in RPS. Surprisingly, the concentration of PI, PII and gracillin as diosgenyl saponins was higher than that of pennogenyl saponins in the liver and lung. Besides, plasma protein binding rate of PII was higher than that of PVII. Conclusion: These findings suggested that PVII, PH, PVI, PI, PII and gracillin are regarded as the Q-markers of RPS in liver cancer pulmonary metastasis. The concentration of PI, PII and gracillin as diosgenyl saponins was higher than that of pennogenyl saponins in the liver and lung. It would be helpful for understanding the importance of RPS with anticancer activities in the future. Graphical abstract: Image 1